Implementing the "SMART" Framework for Effective Management of Inactive Archives: A Case Study of the Faculty of Economics, Universitas Negeri Semarang - Rohmawati; Ahmad Saeroji; Maya Sari; Moch Faizal Rachmadi (Soshum: Jurnal Sosial dan Humaniora, 2025)
Effective archive management is essential for organizations, companies, and agencies to support administrative processes, decision-making, and policy development. This study aims to enhance the structuring and management of inactive records at the Faculty of Economics and Business (FEB), Universitas Negeri Semarang (UNNES) through the implementation of the SMART (Selective, Comprehensive, Active, Responsive, and Trusted) method. The research follows the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model, which provides a structured and systematic approach suitable for archival research. The findings indicate a significant transformation in archival management, making it more organized, systematic, and integrated. FEB UNNES has adopted a barcode-based classification system, facilitating more efficient retrieval of records. Identified inactive records have been systematically arranged in the FEB Record Center, located in the L3 Building, 2nd Floor. Additionally, 76 types of records have been identified for potential destruction, with consultations conducted with the UNNES Archives Technical Management Unit to ensure proper procedures. Five sets of basic data files from 2017–2021 have been submitted for disposal. The implementation of the SMART model enhances accessibility, systematization, and digitalization in archive management at FEB UNNES, providing a more efficient and reliable archival system.